REJECTIVE BEHAVIORS TOWARD AFRICAN-AMERICAN SLAVES IN COLSON WHITEHEAD’S THE UNDERGROUND RAILROAD NOVEL - Khatimah, Husnul; Sili, Surya; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This study aimed to identify types of rejective behavior that depicted in Colson Whitehead’s The Underground Railroad and analyzed how the African-American slaves react toward these rejective behaviors. To conduct this research, the researcher used qualitative method, content analysis approach and multicultural criticism. The data source of this research was The Underground Railroad novel written by Colson Whitehead. The data were taken in the forms of words, sentences, clauses, phrases and narration that related to act of rejective behaviour experienced by African-American slaves and their reaction toward this rejective behaviour that suitable with Allport’s rejective behaviour theory and responses to rejective behavior theory. As analyzed, the results showed that all types of rejective behaviors were depicted in the novel. First, verbal rejection where in the action there were an indication of verbally insult like name calling, making fun of cultural makers and joking about physical attribute. Second, discrimination where in the action there were an indication of segregation and unfairly treatment between whites and blacks. Last, physical attack where in the action there were the indications of violence acts. Furthermore, the result also showed how African-American slaves react to these rejective behaviors that they experienced.